Urban planning and mobility styles: more than a relation - Vitale Brovarone, Elisabetta (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The relation between transport and land use is a widely debated issue. As many authors outlined and the common sense suggests, land use and transport are two sides of the same coin. With few exceptions, people travel in order to reach places where they can carry out their activities. If one the one side talking about land use and mobility may seem redundant, this kind of feeling of redundancy and yet the great and growing interest of the scientific community reveal the complexity of this relation. Does the spatial structure of cities influence mobility styles? Besides some theoretical assumptions, many researches tried to answer this question and to find evidences for it, especially in terms of causality. Most of the scientific literature about the influence of urban structure on mobility can be found within the debate over compact city and urban sprawl. Two main goals can be identified for these studies (the first being by some means functional to the second): a deep understanding of the relation between the two fields and the detection of a “good” urban structure. Moreover, this relation is analyzed in order to devise and support integrated land use and transport strategies meant to counter sprawl and de-territorialization processes and to get to a more balanced modal share. Research efforts, those of the last decade in particular, are then focused on finding causal relations between land use and transport, in order to support - or in some cases to undermine - integrated policies (e.g. Transit Oriented Development in the USA or the ABC policy in the Netherlands). Despite the amount and variety of studies devoted to this topic, this relation is still far from being understood and empirically proven, turning out to be a very complex and disputed issue. Considering the evolution of the literature on the relation between the spatial structure of cities and the inhabitants’ travel behaviour, a gradual softening of positions can be identified, so that unambiguous positions are disappearing. Analyzing the literature about the relation between transport and land use, the paper will identify the main emerging problematic issues and controversies. Not denying the importance of causal relations between urban structure and mobility styles, the question that will be addressed, and that underlies the analysis, is whether the evidence for this relation should be considered as a staging post for devising policies to counter de-territorialization processes and unsustainable lifestyles or not.